AHARONOV-BOHM EFFECT IN NON-UNIFORM QUANTUM DOTS - Gélvez, Adriana Lucia; Gutierrez, Willian; Rodríguez Prada, Fredy (Innovaciencia, 2016)
Introduction: Recently, research in the field of condensed matter have been focusing on the study of structures fabricated by different techniques of crystal growth, especially semiconductor materials this has aroused great interest in the theoretical study and technological performance of the important properties that display particle systems confined in quantum dots with differentmorphologies (semiconductor nanostructures zero - dimensional). A special interest in the field of low - dimensional systems is the study of opto - electronic properties of quantum dots with irregular shapes. Quantum Rings, especially, are semiconductor structures having axial symmetry and have a cavity in the region between the inner and outer radius. Due to the periodic confinement the behavior of charge carriers in such structures should have a different character in the presence of an external magnetic field, as with the so-called Aharonov- Bohm Effect (AB). This phenomenon is usually observed when a charged particle confined in a low dimensional system is affected by an external electromagnetic field. Materials and methods: We analyzes the effect of morphological irregularity of lenticular- like and crater-like quantum dots, and the effect of a magnetic field applied in the growth direction on the energy spectrum of an electron confined in these structures. Results and discussion: Structural defects are modeled by functions in cylindrical coordinates, which presented analytical solutions for the isotropic case. Subsequently, the results of energy states of the electron in symmetrical structures allow obtain the energy to complete and complex problems by using numerical methods, as exact diagonalization and series expansion. Conclusions: We present the energy levels of an electron as a function of magnetic field intensity and shown different behaviors for both types of QDs considered, mainly AB oscillations in crater-like quantum dots, characteristic phenomena of one-dimensional quantum rings. This effect is due to the higher probability of finding the electron in the outer border of the structure, because this region has the lowest quantum confinement.